A prospective study to find out the most cost effective preoperative prophylactic antibiotic regime in elective abdominal routine surgeries - Narendra N Ganguly; Rituparna Phukan Ray; M Lahka; Aisha Siddiqui (International Journal of Medical Research and Review, 2016)
Introduction: Anti microbial prophylaxis before any elective surgery is a preferred deterrent to post operative surgical site infection now. A study was undertaken to evaluate the efficacy of preoperative prophylaxis in our hospital setting. We have used different antibiotics, two being from the cephalosporin class, one from the fluoroqiuinolones and anti beta lactamases in combination along with metronidazole. These were used in different combinations and for different durations. The aim was to find out the best and most economical pre operative prophylaxis in our surgical practice.Methods: A total of 138 patients (above 16 years) were taken for the study. It was a randomized and blind study. Patients were prospectively analysed. First, the patients were divided into two groups, those who would receive a single dose of antibiotic at incision and those who received two more doses after the dose at incision. Next, the patients were analysed depending on operation room condition wise. The open elective as well as the laparoscopic elective procedures done in an OT condition where emergencies are undertaken as well as open and lap cases done in OTs where only elective cases are undertaken. The routine practice of preoperative bath, preoperative preparations of the area with iodophores and spirit, operating under normothermia and hydration were as per the institutional philosophy and common to all the patients. Cefotaxime+ Sulbactum, Ofloxacin + Metronidazole, Cefepime+ Tazobactum.Result: Keeping the outcome of the study in mind all the materials was analysed and statistical analysis done and confidence intervals were noted. The single dose pre operative prophylaxis scored over three doses regime in all the cases for lap surgery irrespective of OT condition. Three doses regime worked better in combined OT condition for the open elective procedures. The study also revealed the most economic choice for routine elective abdominal surgery.Conclusion: Multiday and antibiotics use for a prolonged period is not advisable these days after a routine elective abdominal surgery. Single dose injection of antibiotics at a proper time is good enough for preventing postoperative surgical site infection after a routine Laparoscopic surgery. Three doses regime is better in open surgical cases performed in OTs where emergency procedures are undertaken. It is advisable to use the most cost effective regime to reduce the healthcare cost in the country.